2014
DOI: 10.1016/j.bbamcr.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-C modulates proliferation and chemoresistance in acute myeloid leukemic cells through an endothelin-1-dependent induction of cyclooxygenase-2

Abstract: High-level expression of vascular endothelial growth factor (VEGF)-C is associated with chemoresistance and adverse prognosis in acute myeloid leukemia (AML). Our previous study has found that VEGF-C induces cyclooxygenase-2 (COX-2) expression in AML cell lines and significant correlation of VEGF-C and COX-2 in bone marrow specimens. COX-2 has been reported to mediate the proliferation and drug resistance in several solid tumors. Herein, we demonstrated that the VEGF-C-induced proliferation of AML cells is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…ET-1 levels in SMMC-7221 cells were downregulated via the introduction of targeted ET-1 shRNA. The results of the present study demonstrated that silencing ET-1 inhibited the proliferation of SMMC-7221 cells and tumor growth, which is concurrent with the findings of previous studies (22,26,27).…”
Section: Discussionsupporting
confidence: 81%
“…ET-1 levels in SMMC-7221 cells were downregulated via the introduction of targeted ET-1 shRNA. The results of the present study demonstrated that silencing ET-1 inhibited the proliferation of SMMC-7221 cells and tumor growth, which is concurrent with the findings of previous studies (22,26,27).…”
Section: Discussionsupporting
confidence: 81%
“…Emerging evidence indicates that the VEGF ligands act as survival factors for tumour cells that express the receptors343536. In leukaemia cells, the VEGF family opposes apoptosis via induction of the anti-apoptotic protein Bcl-2 and blockade of VEGFR3 induces chemosensitisation in ovarian cancer cells3738.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging data indicate that the VEGF ligands act as survival factors for tumour cells that express the receptors545556. In colorectal cancer cells, VEGFA depletion reduces cell survival and enhances chemosensitivity via blockade of AKT and ERK1/2 pathways57.…”
Section: Discussionmentioning
confidence: 99%